التعارض بين السماع والقياس وموقف النحويين منه (Journal of Humanitarian and Applied Sciences, 2023)
If there is a conflict between listening and analogy, then the audible is uttered according to what was said, and it is not permissible to compare others with it. The views of the grammarians varied in what is heard about the Arabs by other than analogy. Some of them mentioned that this is wrong about the Arabs, while others mentioned that it is not Arab speaking, and some of them singled it out for the Arabs.